2019
DOI: 10.1186/s40163-019-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of weapons of influence, life domains, and demographic-targeting in modern spam: an age-comparative perspective

Abstract: Spam has been increasingly used for malware distribution. This paper analyzed modern spam from an age-comparative perspective to (i) discover the extent to which psychological weapons of influence and life domains were represented in today’s spam emails and (ii) clarify variations in the use of these weapons and life domains by user demographics. Thirty five young and 32 older participants forwarded 18,605 emails from their spam folder to our study email account. A random set of 961 emails were submitted to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In particular, frequent experiences with financial scams in everyday life may have transferred knowledge into the study and could be underlying "resilience" to these types of attacks. Consistent with this speculation, in our independent study of naturally received spam emails by young and older Internet users, financial spam emails were most prevalent while legal spam emails were least prevalent (Oliveira et al 2019).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In particular, frequent experiences with financial scams in everyday life may have transferred knowledge into the study and could be underlying "resilience" to these types of attacks. Consistent with this speculation, in our independent study of naturally received spam emails by young and older Internet users, financial spam emails were most prevalent while legal spam emails were least prevalent (Oliveira et al 2019).…”
Section: Discussionsupporting
confidence: 60%
“…This could explain the low effectiveness of health-related emails in our study. Supporting this possibility, in an independent study we showed that older compared to young Internet users were more likely to receive spam emails referring to health in their everyday lives (Oliveira et al 2019).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This included informing the participants about the research aims prior to their participation and conducting the experiment in a laboratory setting. These factors have been shown to naturally arouse suspicion levels and induce System 2 (i.e., analytical) cognitive processing (Caputo et al, 2014 ; Oliveira et al, 2019 ). Moreover, participants had no time constraints when completing the phishing detection task.…”
Section: Discussionmentioning
confidence: 99%